ChemInform Abstract: Rb as an Alternative Cation for Templating Inorganic Lead‐Free Perovskites for Solution Processed Photovoltaics. Issue 52 (6th December 2016) - Mulmudi, Hemant Kumar; et al.,
Abstract: Rb is used as a template for the formation of layered Sb perovskites via solution processing.